Brief daily access to cafeteria‐style diet impairs hepatic metabolism even in the absence of excessive body weight gain in rats. Issue 7 (28th May 2020) - Giudetti, Anna Maria; Micioni Di Bonaventura, Maria Vittoria; Ferramosca, Alessandra; Longo, Serena; Micioni Di Bonaventura, Emanuela; Friuli, Marzia; Romano, Adele; Gaetani, Silvana; Cifani, Carlo
Abstract: Numerous nutritional approaches aimed at reducing body weight have been developed as a strategy to reduce obesity. Most of these interventions rely on reducing caloric intake or limiting calories access to a few hours per day. In this work, we analyzed the effects of the extended (24 hours/day) or restricted (1 hour/day) access to a cafeteria‐style (CAF) diet, on rat body weight and hepatic lipid metabolism, with respect to control rats (CTR) fed with a standard chow diet. The body weight gain of restricted‐fed rats was not different from CTR, despite the slightly higher total caloric intake, but resulted significantly lower than extended‐fed rats, which showed a CAF diet‐induced obesity and a dramatically higher total caloric intake. However, both CAF‐fed groups of rats showed, compared to CTR, unhealthy serum and hepatic parameters such as higher serum glucose level, lower HDL values, and increased hepatic triacylglycerol and cholesterol amount. The hepatic expression and activity of key enzymes of fatty acid synthesis, acetyl‐CoA carboxylase (ACC), and fatty acid synthase (FAS), was similarly reduced in both CAF‐fed groups of rats with respect to CTR. Anyway, while in extended‐fed rats this reduction was associated to a long‐term mechanism involving sterol regulatory element‐binding protein‐1 (SREBP‐1), in restricted‐fed animals a short‐term mechanism based on PKA and AMPK activation occurred in the liver. Furthermore, hepatic fatty acid oxidation (FAO) and oxidative stress resulted significantly increased in extended, but not in restricted‐fed rats, as compared to CTR. Overall, these results demonstrate that although limiting the total caloric intake might successfully fight obesity development, the nutritional content of the diet is the major determinant for the health status.